Outcomes of Ischemic Stroke and Associated Factors Among Elderly Patients With Large-Artery Atherosclerosis: A Hospital-Based Follow-Up Study in China - Wu, Qianqian; Cui, Jingjing; Xie, Yuanli; Wang, Min; Zhang, Huifang; Hu, Xiaofei; Jiang, Fenghua (Frontiers in Neurology, 2021)
Large-artery atherosclerotic (LAA) stroke is the most common subtype of ischemic stroke. However, risk factors for long-term outcomes of LAA stroke in the elderly Chinese population have not been well described. Therefore, we aimed to assess outcomes and risk factors at 3, 12, and 36 months after LAA stroke onset among stroke patients aged 60 years and older. All consecutive LAA patients aged ≥ 60 years were prospectively recruited from Dongying People’s Hospital between January 2016 and December 2018. The clinical features and outcome data at 3, 12, and 36 months after stroke were collected. Differences in outcomes and relationship between outcomes and risk factors were assessed. A total of 1772 patients were included in our study (61.7% male, 38.3% female). The rates of mortality, recurrence, and dependency were 6.6%, 12.6%, and 12.6%, respectively, at 3 months after stroke onset. The corresponding rate rose rapidly at 36 months (23.2%, 78.7%, and 79.7%, respectively). We found a positive association between age, FPG level, and stroke severity and all outcomes at 3, 12, and 36 months after stroke onset. Hypersensitive CRP level was an independent risk factor for mortality at different follow-up times. WBC level was associated with both stroke recurrence and dependency at 3 months. In contrast, a higher level of LDL-C within the normal range was a protective factor for recurrence and dependency at shorter follow-up times. These findings suggest that it is necessary to control the risk factors of LAA to reduce the burden of LAA stroke. Especially, this study provides a new challenge to explore the possibility of lowering LDL-C level for improved stroke prognosis.